Emotional experience of people with advanced liver disease: Secondary data analysis. (December 2020) - Gray-Renfrew, Alexandra; Kimbell, Barbara; Finucane, Anne
Introduction: Patients with advanced liver disease live mainly in the community with treatment of complications provided for in-hospital. The illness trajectory of advanced liver disease is uncertain and most do not have access to end of life care. Gaps in knowledge and understanding of the patient experience of this condition have been identified. Methods: Secondary analysis of 15 transcripts from in-depth interviews with people with advanced liver disease collected as part of a previous longitudinal study on the experience of liver disease. Transcripts were thematically analysed for emotional content. Results: Fear, anger, sadness and guilt clearly featured in the person's experience of advanced liver disease. Certain causal factors were identified as provoking these emotional responses, including shock of diagnosis, uncertainty concerning illness, lack of coordinated care, worrying symptoms and sudden death. Humour emerged as a coping mechanism. Conclusion: People living with advanced liver disease experience distressing emotions. It is helpful for clinicians, nurses and other healthcare support staff to have an appreciation of the person's emotional concerns in order to provide holistic care typical of a palliative approach.